2015
DOI: 10.1016/j.nicl.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Linked alterations in gray and white matter morphology in adults with high-functioning autism spectrum disorder: A multimodal brain imaging study

Abstract: Growing evidence suggests that a broad range of behavioral anomalies in people with autism spectrum disorder (ASD) can be linked with morphological and functional alterations in the brain. However, the neuroanatomical underpinnings of ASD have been investigated using either structural magnetic resonance imaging (MRI) or diffusion tensor imaging (DTI), and the relationships between abnormalities revealed by these two modalities remain unclear. This study applied a multimodal data-fusion method, known as linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 126 publications
(175 reference statements)
6
52
4
2
Order By: Relevance
“…White matter abnormalities in early adulthood in ASD appear to converge towards lower FA, and, despite being scarcely reported, also higher MD and RD in various tracts [Bloemen et al, 2010;Conturo et al, 2008;Gibbard et al, 2013;Itahashi et al, 2015;Langen et al, 2012;Mueller et al, 2013;Thakkar et al, 2008]. However, other studies reported no differences in FA and/or MD [Bakhtiari et al, 2012;Kirkovski et al, 2015;Pugliese et al, 2009;Thomas et al, 2011], or even higher FA [Roine et al, 2013] in young adults with ASD.…”
Section: Introductionmentioning
confidence: 86%
“…White matter abnormalities in early adulthood in ASD appear to converge towards lower FA, and, despite being scarcely reported, also higher MD and RD in various tracts [Bloemen et al, 2010;Conturo et al, 2008;Gibbard et al, 2013;Itahashi et al, 2015;Langen et al, 2012;Mueller et al, 2013;Thakkar et al, 2008]. However, other studies reported no differences in FA and/or MD [Bakhtiari et al, 2012;Kirkovski et al, 2015;Pugliese et al, 2009;Thomas et al, 2011], or even higher FA [Roine et al, 2013] in young adults with ASD.…”
Section: Introductionmentioning
confidence: 86%
“…Additionally, white matter networks adjacent to basal ganglia correlated with obsessive-compulsive symptoms. Another study(93) reported linked alterations in GM and WM morphology in adults with high-functioning autism spectrum disorder (ASD) via linked ICA, ASD patients showed decreased GM volumes in bilateral fusiform gyri, orbitofrontal cortices, and pre-/post-central gyri, which were linked with a pattern of decreased FA in tracts of inferior longitudinal fasciculi, inferior fronto-occipital fasciculi, and corticospinal tracts, all bilaterally.…”
Section: Review Of Fusion Studies Focused On Psychopathologymentioning
confidence: 99%
“…However, note that our results did not show a main effect of group (i.e., group differences in gray matter volume regardless of Eyes Test score) in the TPJ, which is consistent with several structural MRI studies in adults with ASD (Abell et al, 1999; McAlonan et al, 2002; Schmitz et al, 2006, 2008; Wilson et al, 2009; Dziobek et al, 2010; Toal et al, 2010; Ecker et al, 2013; Lai et al, 2013; Bernhardt et al, 2014; Riedel et al, 2014; Balardin et al, 2015; Gebauer et al, 2015; Itahashi et al, 2015; Libero et al, 2015; for a review see Yang et al, 2016). Our results suggest that individuals with ASD may have atypical brain–behavior associations that cannot be detected using structural MRI data alone.…”
Section: Discussionmentioning
confidence: 94%